Pupillometric evidence for the locus coeruleus-noradrenaline system facilitating attentional processing of action-triggered visual stimuli - Kihara, Ken; Takeuchi, Tatsuto; Yoshimoto, Sanae; Kondo, Hirohito M.; Kawahara, Jun I. (Frontiers in Psychology, 2015)
It has been argued that attentional processing of visual stimuli is facilitated by a voluntary action that triggers the stimulus onset. However, the relationship between action-induced facilitation of attention and the neural substrates has not been well established. The present study investigated whether the locus coeruleus-noradrenaline (LC-NA) system is involved in this facilitation effect. A rapid serial visual presentation paradigm was used to assess the dynamics of transient attention in humans. Participants were instructed to change a digit stream to a letter stream by pressing a button and specifying successive targets of four letters. Pupil dilation was measured as an index of LC-NA function. Accuracy of target identification was better when the temporal delay between participants’ key press and target onset was 800 ms than when targets appeared just after the key press or when targets appeared without key press. Accuracy of target identification was positively correlated with both the peak amplitude of pupil dilation and the pupil size at the time of the key press. These results indicate that target identification in the visual task is closely linked to pupil dilation. We conclude that the LC-NA system plays an important role in the facilitation of transient attention driven by voluntary action.